Microbiological profile of respiratory tract infections in children with neurological impairment - Romero, Ray Braga; Costa, Ana Laura Rezende; Vilela, Dalila Morais; Carvalho, Mariana Sanches de; Nunes, Renato Alves (Research, Society and Development, 2024)
The microbiological profile of respiratory infections in children with neurological impairment (CNI) may differ from that of the general population, which is why this study is interested in investigating the main bacterial agents that affect the respiratory tract of CNI compared to the general compared to the general pediatric population. To this end, the aim of this article is to present a systematic review of the microbiological profile of respiratory tract infections in children with neurological impairment. Initially found 34 articles in the Pubmed, Cochrane and BvSalud databases, published between 2014 and 2024. Of these, articles covering bacterial pneumonia were included, and review articles without meta-analysis were excluded, master's dissertations and doctoral theses that did not contain an observational study; a total of 5 articles were used. The The main causative agents of bacterial pneumonia vary according to the child's age and condition of the child, with Pseudomonas aeruginosa and Staphylococcus aureus predominate in CNI, unlike other children, in whom commonly develop pneumonia due to Streptococcus pneumoniae and, less commonly, Staphylococcus aureus. The microbiological profile of respiratory infections in children with neurological syndromes differs from that of the general population due to their susceptibility to atypical and sometimes more severe infections. However, more studies are needed on this subject clarification is needed in the current literature.